Global Economic History : A Very Short Introduction - Allen, Robert C., 1947- (Oxford, New York Oxford University Press, 2011)
Why are some countries rich and others poor? In 1500, global income differences were small, but disparities have grown dramatically since Columbus reached America. In this Very Short Introduction, Robert C. Allen shows how the interplay of geography, globalization, technological change, and economic policy has determined the wealth and poverty of nations. Allen shows how the industrial revolution was Britain's path-breaking response to the challenge of globalization. Western Europe and North America joined Britain to form a club of rich nations, pursuing four policies--creating a national market by abolishing internal tariffs and investing in transportation, erecting an external tariff to protect their fledgling industries from British competition, creating banks to stabilize the currency and mobilize domestic savings for investment, and promoting mass education to prepare people for industrial work.
Include Index and Illustration
Keywords: Economic history -- Economic indicators -- International economic relations